Antiviral Use and Health Care Use Among US Patients With Rheumatoid Arthritis and Influenza in Three Influenza Seasons, 2016‐2019. Issue 7 (12th May 2022) - Neuberger, Edward E.; To, Tu My; Seetasith, Arpamas; Arndorfer, Stella M.; Wallick, Chris J.
Abstract : Objective: Patients with rheumatoid arthritis (RA) are vulnerable to severe complications of influenza. We assessed whether health care resource use (HRU) and costs differed between patients with RA and influenza who received antiviral medication compared with matched patients with RA and influenza not receiving antiviral therapy. Methods: This was a retrospective US health insurance claims analysis over three influenza seasons (each October to April) in 2016‐2019. Adults with RA and a subsequent diagnosis of influenza were included. Treated patients (receiving antiviral influenza treatment within 2 days of diagnosis) and untreated patients were propensity score matched using baseline covariates. HRU and costs were assessed for inpatient, emergency department (ED), and outpatient visits and compared between cohorts using χ 2 tests and t tests. Results: After matching, 2638 treated and 1319 untreated patients were included. For treated versus untreated patients, the mean number of all‐cause outpatient visits was 0.96 versus 1.21 during 14 days of follow‐up ( P  < 0.001) and 1.94 versus 2.24 over 28 days ( P  = 0.001), respectively. Over 28 days, the mean number of all‐cause ED visits was lower among treated (0.23) than untreated (0.30) patients ( P  = 0.042). The mean number of respiratory‐related outpatient visits was significantly lower for treated versus untreated patients, and mean costs for these visits were $17.89 versus $35.27 over 14 days ( P  < 0.001) and $28.92 versus $48.77 over 28 days ( P  < 0.001) for treated versus untreated patients, respectively. Conclusion: Our findings demonstrate that prompt antiviral treatment after influenza diagnosis may reduce HRU and costs in patients with RA.